Wehali: The Female Land Traditions of a Timorese Ritual Centre - Therik, Tom (Comparative Austronesian Series, 2023)
Wehali defines itself as the ritual centre of the island of Timor. As a ritual centre, Wehali continues to be the residence of a figure of traditional authority on whom, in the 18th century, the Dutch conferred the title of Kaiser (Keizer) and to whom the Portuguese gave the title of Emperor (Imperador). At one time, Wehali was the centre of a network of tributary states, which both the Dutch and Portuguese regarded as paramount to the political organisation of the island. This book is a study of Wehali in its contemporary setting as it continues to maintain its rituals and traditions. Significantly, Wehali is a 'Female' centre and its 'Great Lord' is considered to be a 'Female' lord. Whereas other Timorese societies are organised along male lines, in Wehali, all land, all property, all houses belong to women. Men are exchanged as husbands in marriage. Wehali is thus considered to be the 'husband-giver' to the surrounding realms on the island that look to its inner power as their source of life.